Software para facturación electrónica sobre plataforma Azure utilizando la metodología desarrollo rápido de aplicaciones (RAD) - Avalos Trujillo, Kevin Germán (2024)
This thesis addresses the development of an electronic billing software on the Azure platform, applying the Rapid Application Development (RAD) methodology. The main objective of this project was to design, develop and implement an efficient and scalable electronic invoicing software that meets the specific needs of a modern company. Extensive literature research was conducted on the RAD methodology and relevant information was collected to support the development process. The e-invoicing software developed in Azure followed an iterative and user-centered approach, allowing rapid delivery of functional prototypes and agilely adapting to changes in business requirements. Robust security measures were implemented to protect sensitive data, and system scalability and performance was optimized using built-in Azure services. The end result was a highly efficient and reliable electronic invoicing software, capable of effectively managing business transactions, optimizing billing processes and improving the company's operational efficiency. The RAD methodology proved to be an invaluable tool for the success of the project, allowing for rapid and effective implementation of the software and guaranteeing customer satisfaction reducing the time and resources required to complete the development stages with a success rate of 100%, a response time of 6.82 seconds, and a productivity indicator of 2.8 (features developed) / (month). In conclusion, the development of the electronic billing software in Azure using the RAD methodology represents a significant step towards modernization and efficiency in the company's financial management.